EFFECT OF HYDROTHERMAL TREATMENT DURATION ON THE PHOTOCATALYTIC PERFORMANCE OF ZINC OXIDE (ZNO) NANORODS FOR WASTEWATER PURIFICATION: PENGARUH LAMA PERLAKUAN HIDROTERMAL TERHADAP KINERJA FOTOKATALIK ZINC OXIDE (ZNO) NANORODS UNTUK PEMURNIAN AIR LIMBAH - Muhammad Fajar Setiawan; Iwan Sugihartono; Nurfina Yudasari (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
Zinc Oxide (ZnO) has been extensively developed in the field of wastewater treatment as a photocatalyst to degrade dye contaminants. The photocatalytic efficiency of ZnO can be enhanced by modifying its nanostructure, particularly by synthesizing ZnO in the form of nanorods. In this study, a simple hydrothermal method was used to synthesize ZnO nanorods and evaluate their effectiveness in degrading textile dye wastewater, using rhodamine B (RhB) and methylene blue (MB) as model pollutants. Zinc sheets with a thickness of 0.1 mm were treated hydrothermally in an autoclave containing 50 ml of deionized water at 95°C for 8, 16, and 24 hours. Subsequently, each sample was analyzed for its morphological and structural characteristics before being immersed in RhB and MB solutions with a concentration of 5 ppm and exposed to UV light at a wavelength of 352 nm and an intensity of 900–1000 mW/cm2. The degradation rates of RhB were found to be 63.4% for ZnO-8, 94% for ZnO-16, and 79.9% for ZnO-24, while for MB, they were 74.3% for ZnO-8, 75% for ZnO-16, and 68% for ZnO-24. These results indicate that ZnO synthesized hydrothermally for 16 hours exhibited superior degradation performance for both rhodamine B and methylene blue compared to the 8-hour and 24-hour treatments.